2011
DOI: 10.4314/njp.v38i1.72242
|View full text |Cite
|
Sign up to set email alerts
|

HIV infection in orphanages in South Western Nigeria

Abstract: A total of 190 children were enrolled from 7 homes with males accounting for 89 (46.8%). The main reasons for admission into the orphanages were; orphaned 85 (44.7%), abandoned 79 (41.6%) and mental illness in mother 11(5.8%). Two children were HIV positive, giving a prevalence rate of 1.05%. All the homes (100%) had a policy which excluded admission of HIV positive children but seldom carried out HIV testing at entry. Fear of disease transmission to others was the reason given for not admitting such children.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
5
1
Order By: Relevance
“…Infants and children having CD4+ count lower than 25% are recommended for anti-retroviral treatment 5,6 This child was registered in HIV Clinic for further management. The observed HIV prevalence in this study was contrary to the work 7 that reported a prevalence of 1.05% in seven orphanage homes in the South Western Nigeria. A higher prevalence of 7.2% was reported for HIV infection among pregnant antenatal women in Benin City 8 although it was in a different population.…”
Section: Discussioncontrasting
confidence: 99%
“…Infants and children having CD4+ count lower than 25% are recommended for anti-retroviral treatment 5,6 This child was registered in HIV Clinic for further management. The observed HIV prevalence in this study was contrary to the work 7 that reported a prevalence of 1.05% in seven orphanage homes in the South Western Nigeria. A higher prevalence of 7.2% was reported for HIV infection among pregnant antenatal women in Benin City 8 although it was in a different population.…”
Section: Discussioncontrasting
confidence: 99%
“…In Nigeria, out-of-home care is provided mainly through residential institutions (Oladokun, Brown, Jacob, & Osinusi, 2011). These institutions, referred to as orphanages and children’s homes, are owned by the government, private individuals, or NGOs regulated by the Child Rights Act (2003), through the Federal Ministry of Women Affairs and Social Development (FMWA&SD).…”
mentioning
confidence: 99%
“…From some studies conducted in Africa (e.g., Bond, 2010; Ibeh, 2011; Oladokun et al, 2011), the major reasons for children going into institutional or residential care include abandonment, war, poverty, displacement, urbanization, and migration. Since adoption and formal foster care are not commonly practiced in Nigeria, largely due to the negative sociocultural perceptions most families hold, most of these children end up living in residential homes (Graham & Saater, 2017).…”
mentioning
confidence: 99%
“…This study reveals that the magnitude of HIV infection in vulnerable children is enormous. [19,20]. These figures are comparatively lower than our studies and reasons for these include the fact that our study included both institutional and household VC; in addition to the variability of incidence within adult population by states within Nigeria as pediatric HIV infections may reflect the adult burden of the diseases.…”
Section: Discussionmentioning
confidence: 60%